Fixed point-based stability analysis of climate and Langevin models - Syed Khayyam Shah; Waleed Eltayeb Ahmed; Ishraq Alabdi; Ayman Alahmade; Khaled Aldwoah; Eltigani I. Hassan (PLoS ONE, 2025)
In this manuscript, the existence and uniqueness of solutions to equations associated with climate change are discussed. For this purpose, we utilize some results from the existing literature to investigate the behavior of these equations. Additionally, the role of fixed point theory in emphasizing the importance of proving the stability and consistency of the models is explored. Several definitions and results, such as the F-contraction, α-F-contraction, rational type (ψ,ϕ)-contraction, and Geraghty type contraction, are recalled from the existing literature to illustrate their theoretical foundations and practical applications.